2011
DOI: 10.1111/j.1365-2052.2011.02205.x
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in the Melanocortin 1 Receptor gene are linked with lightness of fibre colour in Peruvian Alpaca (Vicugna pacos)

Abstract: Melanocortin 1 receptor (alpha melanocyte stimulating hormone receptor) (MC1R) is a gene-controlling melanogenesis in mammals. However, it is not well characterized in alpacas and its association with colour is not known. The aim of this study was to look for polymorphisms in the MC1R gene in Peruvian Huacaya alpacas and to analyse the relationship between MC1R single nucleotide polymorphisms (SNPs) and the variations in the instrumental measurement of colour of alpaca fibre. Sixty alpaca fibre samples from bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 8 publications
1
15
2
9
Order By: Relevance
“…Repeat sequences were inferred to comprised 33.1% of the genome in L. guanicoe, 32.7% in V. vicugna, and 27.02% in L. glama, lower values than in most mammals [11], although such sequences were difficult to assemble most likely due to the limitations of short-read sequencing. Resequencing of seven individuals per species (Additional file 1: Figure S2; Table S8) yielded an average sequence depth of 16-fold after filtering (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) Gb, Additional file 1: Table S9). Resequencing uncovered 21.3 million SNPs and a heterozygous SNP rate of 0.0030 for alpaca, 25.2 million and 0.0023 for vicuña, 16.7 million and 0.0018 for guanaco, and 16.1 million and 0.0020 for llama, indicating a higher overall SNP rate for the Vicugna lineage.…”
Section: De Novo Sequencing Assembly and Resequencingmentioning
confidence: 99%
“…Repeat sequences were inferred to comprised 33.1% of the genome in L. guanicoe, 32.7% in V. vicugna, and 27.02% in L. glama, lower values than in most mammals [11], although such sequences were difficult to assemble most likely due to the limitations of short-read sequencing. Resequencing of seven individuals per species (Additional file 1: Figure S2; Table S8) yielded an average sequence depth of 16-fold after filtering (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) Gb, Additional file 1: Table S9). Resequencing uncovered 21.3 million SNPs and a heterozygous SNP rate of 0.0030 for alpaca, 25.2 million and 0.0023 for vicuña, 16.7 million and 0.0018 for guanaco, and 16.1 million and 0.0020 for llama, indicating a higher overall SNP rate for the Vicugna lineage.…”
Section: De Novo Sequencing Assembly and Resequencingmentioning
confidence: 99%
“…Controlling for such environmental effects during image collection and selecting appropriate color models is thus important to reduce the noise variance. The most commonly used color model is the Commission International d'Eclairage (CIE) L*a*b* system established in 1976 [23], which has been typically employed in genetic studies of pigmentation information collected via spectrophotometers [24][25][26]. In the CIELab color model, any color can be represented by three variables: L*, the lightness-darkness axis; a*, the red-green axis; and b*, the blue-yellow axis, which can be plotted in three-dimensional space [27].…”
Section: Pigmentation Phenotypes: Quantification and Normalization Mamentioning
confidence: 99%
“…The classic grey phenotype is a characteristic dilution of the base colour and can occur over a eumelanic (silvergrey) or pheomelanic (rosegrey) base colour due to unknown mechanisms that govern the variable intensity [28]. In addition, the KRT2 and ASIP genes seem to influence colour determination of alpacas [29,30] whereas the MC1R gene might influence coat lightness [31]. For llamas it was shown that the expression of KIT and MITF was significantly lower in white animals than in coloured ones [32].…”
Section: Introductionmentioning
confidence: 99%